Analysis of swimmers` velocity during the underwater gliding motion following grab start - Elipot, M.; Hellard, P.; Taiar, R.; Boissière, E.; Rey, J. L.; Lecat, S.; Houel, N. (Journal of Biomechanics, 2009)
The purpose of this study was to determine the swimmers` loss of speed during the underwater gliding motion of a grab start. This study also set out to determine the kinematical variables influencing this loss of speed. Eight French national-level swimmers participated in this study. The swimmers were filmed using 4 mini-DV cameras during the entire underwater phase. Using the DLT technique and the Dempster's anthropometric data, swimmer's movement have been identified. Two principal components analysis (PCA) have been used to study the relations between the kinematical variables influencing the loss of speed. The swimmers reached a velocity between 2.2 and 1.9 m s-1 after their centre of mass covered a distance ranging between 5.63 and 6.01 m from the start wall. For this range of velocity, head position was included between 6.02 and 6.51 m. First PCA show that the kinematical parameters at the immersion (first image at which the swimmers` whole body was under water) are included in the first two components. Second PCA show that the knee, hip and shoulder angles can be included in the same component. The present study identified the optimal instant for initiating underwater leg movements after a grab start. This study also showed that the performance during the underwater gliding motion is determined as much by variables at the immersion as by the swimmer's loss of speed. It also seems that to hold the streamlined position the synergetic action of the knee, the hip and the shoulder is essential.